Genealogy Magic in the Perspective of Mufassir Indonesia (QS. Al Baqarah (2): 102 Analysis Study) - Sofyanto Raihan Pratama; Andri Nirwana AN; Agusni Yahya; Abd. Wahid (al-Afkar, Journal For Islamic Studies, 2024)
The history of magic is closely related to the civilization of Prophet Solomon, as well as the two figures named harut and marut. As narrated in the Qur'an, in surah al-Baqarah verse 102. Many scholars and mufasir poured their knowledge to study this verse so as to produce various views on it. Magic is considered a mistake and forbidden thing, as in Islam itself magic is a form of shirk, brings evil, and invites the wrath of Allah Subhanahu wa Ta'ala. However, how can things that are so forbidden and considered wrong, can actually spread widely to various parts of the world. This paper tries to understand the history of magic and various worldviews on magic, to its practice that still exists in modern society. This research is descriptive qualitative research that seeks to describe magical phenomena ranging from their history to their influence on different civilizations. As a result of this research, Allah Subhanahu Wa Ta'ala refuted the accusations against Prophet Solomon for the use of magic through his word, surah al-Baqarah verse 102. While various interpretations of who the real figure of harut and marut is. Behind all that, magic requires something as a payment to achieve its goals, ranging from animals to even human lives. Viewed from any side, magic is present as a test. If used, the practice is only to satisfy man's pseudo-desires and bring destruction to man himself.